Усовершенствование метода подавления теплового шума фото- и видеокамер - Крутько, С. В. (ХНУРЕ, 2019)
Traditionally for suppress of average matrix thermal noise use darkened lines and columns. It's assumed that the thermal noise in all pixels of the matrix is the same. For more effective suppression of thermal noise, it was proposed to subtract the average dark signal taking into account the mask, taking into account the uneven heating of the matrix. The mask was obtained using dark frame filtering with a Gaussian window. It allow to get rid of the noise emission in places of high temperature matrix.